2014
DOI: 10.3324/haematol.2013.096149
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of autologous stem cell transplant-eligible multiple myeloma patients: ten questions and answers

Abstract: F e r r a t a S t o r t i F o u n d a t i o nics and renal impairment. In the era of novel agents, the role of transplant itself is being questioned and trials are ongoing to establish whether transplant can be delayed until after relapse in some patients. The current ongoing studies are aimed towards improving the different steps of the procedure with the aim of further improving efficacy and tolerability. This review addresses a number of questions surrounding the different steps of the transplant procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 75 publications
0
56
0
1
Order By: Relevance
“…The lack of advantage observed in some cases in terms of OS is mainly do to the effective salvage therapy nowadays available, and to the possibility for patients to receive ASCT later in their disease history as a salvage treatment. For this reason some centres nowadays recommend ASCT only for those patients with high-risk features, whilst for standard risk patients a treatment option reserving ASCT for the time of relapse is considered acceptable [59][60][61] . In this contest it has to be emphasised, in patients for whom a delayed ASCT may be considered, the extreme importance of early stem cell collection and cryopreservation; an early stem cell collection is particularly important in those patients receiving lenalidomide based treatments [62,63] .…”
Section: Resultsmentioning
confidence: 99%
“…The lack of advantage observed in some cases in terms of OS is mainly do to the effective salvage therapy nowadays available, and to the possibility for patients to receive ASCT later in their disease history as a salvage treatment. For this reason some centres nowadays recommend ASCT only for those patients with high-risk features, whilst for standard risk patients a treatment option reserving ASCT for the time of relapse is considered acceptable [59][60][61] . In this contest it has to be emphasised, in patients for whom a delayed ASCT may be considered, the extreme importance of early stem cell collection and cryopreservation; an early stem cell collection is particularly important in those patients receiving lenalidomide based treatments [62,63] .…”
Section: Resultsmentioning
confidence: 99%
“…Another three drug combination is comprised of two novel agents (bortezomib, thalidomide or lenalidomide) with dexamethasone-VTD, VRD, etc. [14,15]. Both approaches produce excellent responses; however, a recent trial showed that VRD producing the best response.…”
Section: Transplant Eligible Patientsmentioning
confidence: 99%
“…Older patients also could be candidates if one is in good biological health. Peripheral blood (PBSC) has completely replaced bone marrow as the source of stem cells [14]. It is safe with a mortality risk of 0-1% at most centers.…”
Section: Transplant Eligible Patientsmentioning
confidence: 99%
“…The term "Autologous stem cell transplantation" refers to transplantation of a patient's own stem cells after chemotherapy. It is not curative, but prolongs the overall survival rate and produces complete remission [29]. Allogeneic stem cell transplantation means transplantation of a healthy person's stem cells into the affected patient which may have the potential for cure, but is used in a very low percentage of patients.…”
Section: Initial Therapymentioning
confidence: 99%